Nutritional analysis of two corn hybrids (Zea mays L.) for forage production (Agro Productividad, 2026)
Objective: To characterize and compare the yield and bromatological composition —such as fresh matter, crude protein, and other nutritional indicators— of two corn (Zea mays L.) hybrids, developed under fertigation conditions, at three different plant densities.Design/Methodology/Approach: The experiment was conducted using a factorial experimental design with two factors (hybrids) and three levels (densities).Results: The CEBU hybrid recorded the highest fresh and dry matter yield. According to the bromatological analysis, it also obtained the highest crude protein (CP) values and total ash content. Meanwhile, the A7573 hybrid reached a higher total carbohydrate content.Study Limitations/Implications: The low temperatures recorded during the experiment impacted both the corn plant and crop development cycles.Findings/Conclusions: The agronomic characteristics and nutritional value of evaluated hybrids recorded significant differences. CEBU had a more efficient forage and biomass production in all the evaluated sowing densities (50,000, 62,500, and 83,333 plant ha-1). In the bromatological analysis, CEBU obtained a higher crude protein and ash content than A7573. However, A7573 recorded a higher total carbohydrate content than CEBU.